Synthesis of new methoxy derivatives of trans 2, 3-diaryl-2, 3-dihydrobenzofurans and evaluation of their anti-inflammatory activity. (1st October 2021) - Laurita, T.; Pappalardo, I.; Chiummiento, L.; D'Orsi, R.; Funicello, M.; Santarsiero, A.; Marsico, M.; Infantino, V.; Todisco, S.; Lupattelli, P.
Graphical abstract: Abstract: In the present study we synthesized new methoxy derivatives of trans 2, 3-diaryl-2, 3-dihydrobenzofurans, starting from suitable trans 2, 3-diaryloxiranes, using regio- and stereoselective nucleophilic oxiranyl ring-opening reactions. The compounds were tested as anti-inflammatories in U937 cells. All compounds showed a significant role in inhibiting the NF-κB pathway and were able to restore normal ROS and NO level upon LPS activation. Moreover, regarding inhibition of ACLY, enantioenriched (50% ee ) 7a 50 showed more potency than the racemic counterpart 7a rac, together with a higher reduction of prostaglandin E2 production, thus suggesting a stereoselective interaction in this pathway.